(untitled) (Journal of Dhaka Medical College, 2015)
Retrocaval ureter is a rare congenital urologic anomaly. It occurs due to the persistence of the right subcardinal veins during embryologic development. Its presence should be suspected with the finding of a characteristic S-shaped deformity on intravenous or retrograde pyelography. Today, a definitive diagnosis can be made noninvasively using multi-slice CT imaging or MRI. Intervention is indicated in the presence of functionally significant obstruction leading to pain or renal function deterioration. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 259-261